APLP1 promotes dFoxO-dependent cell death in Drosophila. - Wang, X.; Ma, Y.; Zhao, Y.; Chen, Y.; Hu, Y.; Chen, C.; Shao, Y.; Xue, L. (Apoptosis. An international journal on programmed cell death., 2015)
The amyloid precursor like protein-1 (APLP1) belongs to the amyloid precursor protein family that also includes the amyloid precursor protein (APP) and the amyloid precursor like protein-2 (APLP2). Though the three proteins share similar structures and undergo the same cleavage processing by ?-, ?- and ?-secretases, APLP1 shows divergent subcellular localization from that of APP and APLP2, and thus, may perform distinct roles in vivo. While extensive studies have been focused on APP, which is implicated in the pathogenesis of Alzheimer's disease, the functions of APLP1 remain largely elusive. Here we report that the expression of APLP1 in Drosophila induces cell death and produces developmental defects in wing and thorax. This function of APLP1 depends on the transcription factor dFoxO, as the depletion of dFoxO abrogates APLP1-induced cell death and adult defects. Consistently, APLP1 up-regulates the transcription of dFoxO target hid and reaper-two well known pro-apoptotic genes. Thus, the present study provides the first in vivo evidence that APLP1 is able to induce cell death, and that FoxO is a crucial downstream mediator of APLP1's activity.